STUDENTS' COMMUNICATIVE COMPETENCE SI - Madina KHOLIYOROVA (Scholar Express Journal, 2024)
The main goal of the modern educational process is to develop personal and professional abilities, knowledge, skills and qualifications of future specialists. In the process of higher education, it is important to form the communicative competence of future specialists, that they have not only academic knowledge, but also the ability to positively solve problems in various fields and activities. "Communication" means participation in general cooperation and relations. This concept was introduced into scientific circulation in the 20th century. The process of communication involves the transfer of various information from one person to another, and this process is a cognitive activity carried out mainly with the help of language (if necessary, with the help of other symbolic systems) as a specific form of human interaction, the ability to communicate, cooperate, understand oneself and others is the most valuable quality . determined by personal and psychological preparation, which affects the practice of training specialists in various fields
Keywords: Modern educational; Communication